Lack of Antibacterial Activity of Aqueous and Ethanolic Leaf Extracts of Ziziphus talanai (Blanco) Merr. (Journal of Pharmaceutical Negative Results, 2018)
Objective: The objective of the study is to investigate the phytochemicals and potential antibacterial activity of aqueous and ethanolicleaf extracts of Ziziphus talanai. Materials and Methods: Aqueous and ethanolic crude leaf extracts were subjected to phytochemicalscreening and assayed for their antimicrobial activities via paper disc diffusion method against Escherichia coli and Staphylococcus aureus.Results: Glycosides, condensed tannins, and saponins were found present in the two extracts; however, leucoanthocyanins were additionallydetected in the aqueous extract. Both extracts exhibited no antibacterial activity against E. coli and S. aureus as indicated by the absence ofa zone of inhibition. Conclusion: The results of the present study suggest a limited presence of phytochemicals in the crude aqueous andethanolic leaf extracts of Z. talanai. Water can extract more phytochemicals from Z. talanai leaves than ethanol. However, the results furthersuggest that the phytochemicals from the leaves extracted using water and ethanol do not have antibacterial activities against E. coli andS. aureus. The negative results of the antimicrobial assay using the crude leaf extracts may not be generalized as lack of bioactivity of theother parts of Z. talanai.